Pengaruh Gempa Terhadap Perilaku Jembatan Cable Stayed Tengku Fisabililah Riau Dengan Time History Analysis - Natalia Vin Kristin; Ari Wibowo; Desy Setyowulan; Edhi Wahyuni S. (Rekayasa Sipil, 2018)
Tengku Fisabilillah Riau Bridge is one type of a cable stayed bridge that located in Indonesia. Indonesia is among one of the countries that are prone to earthquakes. Effects of earthquake can change the structure of the bridge. These effects can be analyzed using time history analysis.The first step begins with the modeling of bridge structures. But the dimensions and material specifications of the bridge’s structure has been determined by researcher. After modeling the structure of the bridge is completed, input the data of the time history. This data is taken from the earthquake of Hyogo-Ken Nanbu in Japan. Next, the changes of the structure of the bridge caused by the earthquake such as mode shapes, displacement, and stress that occur will be analyzed. Results of the analysis showed that there were many mode shapes generated, the largest mode shapes is on the Y-axis at the direction of the bridge. For displacement, the maximum displacement occurs direction in Z-axis. The deflection that caused by the earthquake is largest than the allowable maximum deflection of the bridge. While, the maximum stress occurs on the cable. The force which is caused by the earthquake is largest than the allowable maximum force owned section.